2011
DOI: 10.1096/fj.11-181982
|View full text |Cite
|
Sign up to set email alerts
|

3,5‐Diiodo‐L‐thyronine prevents high‐fat‐diet‐induced insulin resistance in rat skeletal muscle through metabolic and structural adaptations

Abstract: The worldwide prevalence of obesity-associated pathologies, including type 2 diabetes, requires thorough investigation of mechanisms and interventions. Recent studies have highlighted thyroid hormone analogs and derivatives as potential agents able to counteract such pathologies. In this study, in rats receiving a high-fat diet (HFD), we analyzed the effects of a 4-wk daily administration of a naturally occurring iodothyronine, 3,5-diiodo-L-thyronine (T2), on the gastrocnemius muscle metabolic/structural pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 48 publications
10
81
2
2
Order By: Relevance
“…In particular, this link is in accordance with animal studies showing that 3,5-T2 was only a third as potent as T3 in suppressing TSH concentrations, and rather high pharmacological 3,5-T2 concentrations are required for TSH suppression (34)(35)(36). However, several animal studies in rodents and other species, for example killifish, indicated that 3,5-T2 interferes with the hypothalamus-pituitary-thyroid axis at several levels such as pituitary, thyroid, and peripheral action, thereby displaying a broad spectrum of mechanisms involved such as classical interaction with TR and also rapid effects at the cell membrane and mitochondria (10,12,14,(34)(35)(36)(37)(38)(39)(40) (for a review, see (3)). Action of 3,5-T2 via these different targets and molecular mechanisms might occur at different 3,5-T2 concentrations and depend on acute or chronic exposure (35,37,40), thus possibly explaining the unexpected bell-shaped relationship with serum TSH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, this link is in accordance with animal studies showing that 3,5-T2 was only a third as potent as T3 in suppressing TSH concentrations, and rather high pharmacological 3,5-T2 concentrations are required for TSH suppression (34)(35)(36). However, several animal studies in rodents and other species, for example killifish, indicated that 3,5-T2 interferes with the hypothalamus-pituitary-thyroid axis at several levels such as pituitary, thyroid, and peripheral action, thereby displaying a broad spectrum of mechanisms involved such as classical interaction with TR and also rapid effects at the cell membrane and mitochondria (10,12,14,(34)(35)(36)(37)(38)(39)(40) (for a review, see (3)). Action of 3,5-T2 via these different targets and molecular mechanisms might occur at different 3,5-T2 concentrations and depend on acute or chronic exposure (35,37,40), thus possibly explaining the unexpected bell-shaped relationship with serum TSH.…”
Section: Discussionmentioning
confidence: 99%
“…According to the promising effects of pharmacological interventions with 3,5-T2 on body weight or blood lipid profile (10,12,14,49), missing associations toward related measures require a clarifying note. To ensure an effect on resting metabolic rate, most of the studies used a daily intraperitoneal injection of 25 lg 3,5-T2 per 100 g body weight (10,12,14), and rather high doses were needed for oral administration in humans and rodents (49,50).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…T 2 , as a nonclassical TH, is able to prevent BW gain when administered i.p. to rats fed a high-fat diet without inducing T 3 -related undesirable side effects (tachycardia, cardiac hyperplasia, and decreased TSH levels), at least at the administered dose (25 mg/100 g BW for 4 weeks) (Lanni et al 2005, De Lange et al 2011, Moreno et al 2011. At this dose, by almost doubling hepatic FA oxidation rate, T 2 efficiently prevented HFD-induced i) hepatic fat accumulation, ii) insulin resistance, and iii) increase in serum triglycerides (TGs) and cholesterol levels (Lanni et al 2005).…”
Section: 5-diiodo-l-thyroninementioning
confidence: 99%